Changing Behavior among Nurses to Track Indwelling Urinary Catheters in Hospitalized Patients - Bona Yoon; Samantha D. McIntosh; Leslie Rodriguez; Alma Holley; Charles J. Faselis; Angelike P. Liappis (Interdisciplinary Perspectives on Infectious Diseases)
Catheter-associated urinary tract infections (CAUTIs) are preventable complications of hospitalization. An interdisciplinary team developed a curriculum to increase awareness of the presence of indwelling urinary catheters (IUCs) in hospitalized patients, addressed practical, primarily nurse-controlled inpatient risk-reduction interventions, and promoted the use of the IUC labels (“tags”). Five thirty-minute educational sessions were cycled over three daily nursing shifts on two inpatient medical floors over a 1-year period; participants were surveyed (n=152) to elicit feedback and provide real-time insight on the learning objectives. Nurse self-reported IUC tagging was early and sustained; after the IUC tag was introduced, there was a significant increase in tagging reported by the end of the block of educational sessions (from 46.2% to 84.6%, P=0.001). Early engagement combined with a targeted educational initiative led to increased knowledge, changes in behavior, and renewed CAUTI awareness in hospitalized patients with IUCs. The processes employed in this small-scale project can be applied to broader, hospitalwide initiatives and to large-scale initiatives for healthcare interventions. As first-line providers with responsibility for the placement and daily maintenance of IUCs, nurses are ideally positioned to implement efforts addressing CAUTIs in the hospital setting.